Crescimento das árvores e fertilidade do solo em plantios de diferentes materiais genéticos de Eucalyptus spp - Scheis, Diego Maicon (2019)
Native of Australia, Timor and Indonesia, eucalyptus is an exotic tree in all other parts of the world. The genus Eucalyptus sp. belongs to the Myrtaceae family and has more than 700 species cataloged. The objective of this study was to evaluate the growth and adaptation of different genetic materials of Eucalyptus spp. to the edaphoclimatic conditions of the region of Dois Vizinhos - Paraná. The five genetic materials selected from Eucalyptus spp. (among species, clones or hybrids) in this work come from clonal and seminal seedlings of the Experimental Station of Forest Sciences of Itatinga, São Paulo (ESALQ/USP), composed of: Eucalyptus urophylla, E. pellita, GFMO27 clone, I224 clone and H13 clone. Each genetic material was planted in a plot of 10 lines and with 16 plants / row, spaced 3 m x 2 m, only H13 was planted with 5 rows and 16 plants/row, in the same spacing. Data were collected in the field: DBH, total height and two crown diameters and, later, calculated basal area, stem volume and crown area, at ages 24, 36, 48, 60, 72 and 108 months, considering each tree as sample unit, in a completely randomized way. The genetic materials were compared by analysis of variance and comparison test of means for DBH, basal area, height, stem volume and crown area. The soil of the area of each genetic material was chemically characterized based on the collection of four soil samples at five different depths (0-5, 5-10, 10-20, 20-40 and 40-60 cm) collected in September 2018 and analyzed in the laboratory. With depth data and content of Al, Ca, Mg, N, MO, pH, P, K and values of DAP (cm), g (m² tree-1), ht (m), v (m³ tree-1) hc (m) and ac (m² tree-1) Pearson correlations were constructed for each depth. The growth of clones H13, I224 and GFMO 27 was superior to the species E. pellita and E. urophylla. The N and MO contents had a strong correlation with the volume of wood. The content of Al+3 presented correlation with DAP. The H13 presented higher values than the other materials in all analyzed variables, reaching an individual volume of 1.27 m³ at 108 months of age. The other genetic materials (GFMO27, I244 and E. urophylla) showed variables in their growth behavior at the different ages of evaluation and E. pellita showed lower growth. In general terms, soil quality is lacking in several chemical elements, which are at low levels in the soil. The recommended genetic material for planting in new regional scale and operational tests are clone H13 and E. urophylla. There is also the possibility of recommending clones GFMO27 and I244, which also present high growth. E. pellita did not show satisfactory growth in Dois Vizinhos, and its planting was not recommended.